2008
DOI: 10.1099/mic.0.2007/014035-0
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthesis of elloramycin in Streptomyces olivaceus requires glycosylation by enzymes encoded outside the aglycon cluster

Abstract: Elloramycin is an anthracycline-like antitumour drug produced by Streptomyces olivaceus Tü 2353. Cosmid cos16F4 has been previously shown to direct the biosynthesis of the elloramycin aglycon 8-demethyltetracenomycin C (8-DMTC), but not elloramycin. Sequencing of the 24.2 kb insert in cos16F4 shows the presence of 17 genes involved in elloramycin biosynthesis (elm genes) together with another additional eight ORFs probably not involved in elloramycin biosynthesis. The 17 genes would code for the biosynthesis o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
48
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(48 citation statements)
references
References 31 publications
0
48
0
Order By: Relevance
“…Analogous to the biosynthesis of elloramycin, L-rhamnose would be synthesized from enzymes encoded elsewhere on the genome (40). The dNDP-L-rhamnose probably constitutes the substrate for a transfer reaction to the CPZ aglycon catalyzed by the putative rhamnosyltransferase Cpz31.…”
Section: Identification and Cloning Of The Caprazamycin Gene Cluster-mentioning
confidence: 99%
“…Analogous to the biosynthesis of elloramycin, L-rhamnose would be synthesized from enzymes encoded elsewhere on the genome (40). The dNDP-L-rhamnose probably constitutes the substrate for a transfer reaction to the CPZ aglycon catalyzed by the putative rhamnosyltransferase Cpz31.…”
Section: Identification and Cloning Of The Caprazamycin Gene Cluster-mentioning
confidence: 99%
“…In addition, formation of a natural compound often relies on the supply of specific precursors provided by genes encoded outside the gene cluster, e.g., deoxysugars (48), isoprenoid derived moieties (20), or other small subunits (45,58). Therefore, the new assembly approach described in this study may help to establish heterologous expression and genetic engineering of scattered gene clusters.…”
Section: Discussionmentioning
confidence: 99%
“…However, biosynthetic gene clusters of rhamnosylated compounds often lack the genes for L-rhamnose formation (9,16,38,54). In the case of elloramycin (48) and spinosyn (41), these genes were identified elsewhere in the genome. Inactivation experiments in Saccharopolyspora spinosa suggested that the gtt, gdh, epi, and kre genes provide the rhamnosyl moiety for both spinosyn and cell wall biosynthesis.…”
Section: Discussionmentioning
confidence: 99%
“…PokMT3 shares 54 % identical aa with FdmN, an Omethyltransferase involved in the fredericamycin biosynthesis in S. griseus, [26] 51 % with TcmN, which is an O-methyltransferase that is involved in the tetracenomycin D3 biosynthesis in S. glaucescens [27,28] and 49 % with ElmNII, which is an O-methyltransferase that is involved in the elloramycin biosynthesis in S. olivaceus. [29] Based on the function of these proteins, PokMT3 is proposed to catalyse the methyl transfer to the phenolic hydroxy group in ring D of POK. In contrast to TcmN, a methyltransferase that also acts as cyclase, a typical cyclase motif could not be found in PokMT3.…”
mentioning
confidence: 99%